Hakikat Kebenaran Sifat Ilmiah, Metode Mendapatkan Kebenaran Ilmiah, Riset Ilmiah dalam Ilmu Manajemen Pendidikan Islam - Putra, Joni; Elizasri, Elizasri; Wardani, Kurnia; Ardeimen, Ardeimen (Jurnal Pustaka Cendekia Pendidikan, 2023)
The problem of the emergence of a knowledge is a very important issue in epistemology, because it will give rise to various answers according to philosophical understanding, whether the answer is a priori (answer that has not been proven by sensory or mental experience) or a posteriori (answer that has been proven by experience and experiment). . Thus, Abbas Hammami is of the opinion quoted by Surojiyo in his book entitled Philosophy that this knowledge is based on objective reality. Problems that occur in humans will feel normal if there is no scientific attitude embedded in them. It is this scientific attitude that encourages people to think critically and radically in dealing with a problem or problem in life which is a source of scientific development. The birth of a new scientific discipline stems from someone's great curiosity to find out the truth about something. The scientific method is a procedure or mechanism in building knowledge from knowledge that is still pre-scientific, with a systematic pattern and adheres to procedural principles and normative techniques, so that scientific validity or validity is produced which can be accounted for. This scientific method must of course be adapted to the nature of the object